2023
DOI: 10.1101/2023.02.26.530085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

2019-20 H1N1 clade A5a.1 viruses have betterin vitroreplication compared with the co-circulating A5a.2 clade

Abstract: Surveillance for emerging human influenza virus clades is important for identifying changes in viral fitness and assessing antigenic similarity to vaccine strains. While fitness and antigenic structure are both important aspects of virus success, they are distinct characteristics and do not always change in a complementary manner. The 2019-20 Northern Hemisphere influenza season saw the emergence of two H1N1 clades: A5a.1 and A5a.2. While several studies indicated that A5a.2 showed similar or even increased an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 63 publications
(116 reference statements)
0
20
0
Order By: Relevance
“…Mutations in the H1N1pdm09 viruses resulted in changes in the HA1 polypeptide, specifically K54Q, A186T, Q189E, E224A, R259K, and K308R. Notably, several of these substitutions occupy both antigenic and receptor binding sites, suggesting that they may have served some compensatory function that allowed the virus to improve its fitness and/or antigenic structure 18,26,27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the H1N1pdm09 viruses resulted in changes in the HA1 polypeptide, specifically K54Q, A186T, Q189E, E224A, R259K, and K308R. Notably, several of these substitutions occupy both antigenic and receptor binding sites, suggesting that they may have served some compensatory function that allowed the virus to improve its fitness and/or antigenic structure 18,26,27 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, several of these substitutions occupy both antigenic and receptor binding sites, suggesting that they may have served some compensatory function that allowed the virus to improve its fitness and/or antigenic structure. 18,26,27 F I G U R E 1 Number of influenza cases in Pakistan by month and year (January 2020-January 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of the 5a.2a clade of H1N1, and the speed with which it predominated, was surprising considering the failure of its parental clade, 5a.2 (Figure 1A). The 5a.2 clade had significantly reduced in vitro fitness compared with the cocirculating 5a.1 clade and their parental 5a clade, including reduced receptor binding diversity, replication, and plaque formation (8). The contrasting success of its progeny 5a.2a clade suggested that there were phenotypic advantages conferred by the 5a.2a clade-defining mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations can alter numerous aspects of viral phenotype, including changes to both fitness and antigenic profile. Changes to fitness can include differences in receptor binding (5)(6)(7)(8), virus replication (8)(9)(10), interactions with innate immunity (11), transmissibility (12)(13)(14), and other characteristics (15). Antigenic profile refers to the regions of a virus which are recognized by host antibodies, and changes to this profile through antigenic drift can alter how the virus appears to the immune system and result in a loss of antibody binding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation